Applications of hydrogel‐based delivery systems in wound care and treatment: An up‐to‐date review. (7th April 2022) - Divyashri, Gangaraju; Badhe, Ravindra V.; Sadanandan, Bindu; Vijayalakshmi, Vaniyamparambath; Kumari, Mamta; Ashrit, Priya; Bijukumar, Divya; Mathew, Mathew T.; Shetty, Kalidas; Raghu, Anjanapura V.
Abstract: Natural wound healing is a highly complex and regulated process. Disruption and barriers to cellular and tissue repair processes contributes to impaired wound healing, including sustained infections. Superficial wound healing requires many factors to work in concrete at the wound site, and thus many treatment options and wound dressings have evolved to address the barriers to wound healing. Biomaterials are proven to encourage the wound healing process by stimulating repair and regeneration of injured tissues and preventing wound infections. A wide range of natural and synthetic hydrophilic and porous formulations such as foams, films, fibers, and hydrogels have been examined for these applications. Among these formulations, polymeric hydrogels have gained considerable interest in the medical applications. They effectively absorb wound exudates and provide a moist environment for aiding the wound healing process. However, chronic wounds that are sustained longer might need supplementary healing features as addendums such as antimicrobials, stem cells, growth factors, peptides, vitamins, and natural compounds. Therefore, when combined with hydrogels healing supporting addendums promote rapid and effective wound healing. Although there have been several advancements in biopolymer‐based hydrogel systems, only limited reviews on various management strategies in wound healing are available in medical research and applications. Therefore, in this review, we have compiled and integrated various hydrogel‐based approaches with the potential to improve chronic wound healing and advance important outcomes. In addition, in‐situ injectable hydrogel preparation that have the advantage of packing patient wounds of different sizes and using 3D printing based tailor‐made hydrogels, and bio‐inks for wound closure applications are also highlighted.